2021
DOI: 10.1111/jace.17940
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and terahertz properties of porous Ba4(Sm,Nd,Bi)28/3Ti18O54 ceramics obtained by sacrificial template method

Abstract: Owing to the phenomenal growth of the communication industry in recent years, higher frequencies and broader bandwidths are required to transmit large amounts of data. As a result, the millimeter-wave and terahertz technologies have gained wide attention. Based on extensive research, microwave dielectric ceramics exhibiting a high relative dielectric constant ( r ), low dielectric loss (tanδ) or high Q × f value (Q = 1/tanδ, f = resonant frequency), and near-zero temperature coefficient of resonant frequency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It has been reported that porosity has a positive effect on Qf value in some microwave dielectric ceramics, because the ceramic phase is lossy, and the air is lossless. 37,38 However, such a direct effect of porosity is not enough for explaining the abnormal dependence of Qf value on sintering temperature, as the differences between the Qf values of the least lossy ceramics and densest ones are as large as 115% and 51% for CaSO 4 and SrSO 4 , respectively, whereas the decreases in relative densities are only 2.5% and 6.8%. Such abnormality in CaSO 4 and SrSO 4 ceramics can be explained by the microstructure evaluation with sintering temperature shown in Figure 3A,D.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that porosity has a positive effect on Qf value in some microwave dielectric ceramics, because the ceramic phase is lossy, and the air is lossless. 37,38 However, such a direct effect of porosity is not enough for explaining the abnormal dependence of Qf value on sintering temperature, as the differences between the Qf values of the least lossy ceramics and densest ones are as large as 115% and 51% for CaSO 4 and SrSO 4 , respectively, whereas the decreases in relative densities are only 2.5% and 6.8%. Such abnormality in CaSO 4 and SrSO 4 ceramics can be explained by the microstructure evaluation with sintering temperature shown in Figure 3A,D.…”
Section: Resultsmentioning
confidence: 99%
“…34 Notably, high 𝜀 𝑟 ceramics often have higher dielectric loss, but introducing air into the composite can effectively reduce this loss, leading to an increase in 𝑄 × 𝑓. 35 As shown in Figure 5, the 𝑄 × 𝑓 values for (1 − x)NBM-xBM ceramics, where x = 0.3-0.6, sintered at varying temperatures for 4 h. At 600 • C, the 𝑄 × 𝑓 value is higher in comparison to the denser ceramics, possibly due to the low permittivity (ε air ≈ 1) and low dielectric loss of air (tanδ ≈ 0). Hence, if the ceramic were to consider as composite and air, the air might bring some positive effect that would increase the 𝑄 × 𝑓 value.…”
Section: St (mentioning
confidence: 99%
“…4,5 As reported, microwave dielectric ceramics are widely used in the fabrication of microwave devices such as antennas, filters, and resonators, 4,6,7 and some of them have excellent dielectric properties in terahertz frequency range. [8][9][10] Moreover, porous structures can reduce both 𝜀 r and tanδ. 11,12 Therefore, highly porous microwave dielectric ceramics may be suitable materials for 6G telecommunication.…”
Section: Introductionmentioning
confidence: 99%